PENGARUH PENDIDIKAN, PELATIHAN, DAN PENGALAMAN MENGAJAR GURU TERHADAP PROFESIONALISME GURU DI SEKOLAH DASAR ( SD ) NEGERI 050662 PERDAMAIAN KECAMATAN STABAT KABUPATEN LANGKAT - Asyhariah . (Jurnal Prodi Fakultas Ekonomi-UISU, 2020)
The formulation in this research is how the influence of education, training and experience teaching teachers to the professionalism of teachers in elementary School (SD) Negeri 050662 Peace District of Stabat District, Langkat, and the purpose of this research is to Know and analyze the influence of education, training and experience teaching teachers to the professionalism of teachers in elementary School (SD) Negeri 050662 District Peace Stabat District Langkat. This research is a quantitative descriptive study. Data collection techniques are conducted through interviews, questionaire questions and documentation studies. Sample in this study as many as 30 teachers in elementary School (SD) Negeri 050662 District Peace Stabat District Langkat. Variables are measured at Likert scale. Hypothesis testing using multiple linear regression analyses through F-test and T-Test. The results of the test in unison showed that the education, training and teaching experience have significant effect on the professionalism of primary school teachers (SD) of the 050662 District peace Stabat with the value of coefficient of determination of 0.554 or 55.4%. In partial, education has a positive and significant effect on the professionalism of elementary school teachers (SD) of state 050662 peace of Stabat subdistrict with a regression coefficient value of 0330 or 33.0%. The training has a positive and significant effect on the professionalism of primary school teacher (SD) Negeri 050662 District Peace Stabat with a regression coefficient value of 0355 or 35.5%. The teaching experience has a positive and significant effect on the professionalism of primary school teacher (SD) Negeri 050662 District Peace Stabat with a regression coefficient value of 0365 or 36.5%. The highest value of a regression coefficient is a teaching experience of 0365 or 36.5%.